Islamic mathematical sciences - Shuriye, Abdi Omar; Daoud, Jamal Ibrahim (2010)
In Islam Mathematics is seen as an important tool for life. The Qur’an considers the rules of mathematics to be a pathway to discover God’s will. This Paper discusses some of the contributions made in mathematics by some Muslim scholars. These remarkable inputs are due to the fact that mathematics is one of the renowned physical sciences which started right from antiquity. The inputs worth discussing in this paper include those of Al–Khawarizmi, Al–Kashi, Al– Khayyam and Al–Khazin. All have invented some vital concepts used in modern day mathematics.